Keterampilan Menulis Puisi Siswa dengan Menggunakan Media Video Kartun - Hidayatika, Uliana; Aprilia, Difa; Rifa, Nisrina Najla; Fitriyah, Mahmudah (DIDAKTIS : Jurnal Pendidikan Bahasa dan Sastra Indonesia, 2024)
This article discusses the poetry writing abilities of grade 4 students at Kedaung Elementary School, Depok. 4th-grade elementary school students' understanding of poetry is still very limited, even when writing poetry individually. Therefore, teaching poetry material in elementary school requires learning media. Cartoon videos are used as learning media for elementary school students because they are very popular. This research was conducted with the aims of finding out the extent of the poetry writing skills of grade 4 elementary school students and analyzing the effectiveness of video media in improving the poetry writing skills of grade 4 elementary school students. Descriptive qualitative methods and open interviews were used in this research. Poetry by 4th grade students at SDN Kedaung, Depok, was used as a data source. Based on this research, it was found that there was an increase in the poetry writing skills of grade 4 elementary school students by using cartoon video media. Of the 30 students, it was found that 24 students experienced an increase in their grades from the first poem to the second poem they wrote. This is proven by the average score for poetry 1 is 65.5 and for writing poetry 2 is 73.2. Based on the results of open interviews, it was found that 21 students felt they had no more difficulty writing poetry after watching cartoon videos. So it is concluded that the use of video media in the form of cartoons is very effective in improving poetry writing skills in students at the elementary school level.